A Study on Web Intelligence for the Internet of Things - Vithya, G.; Naren, J.; Vikas Reddy, Kanakaveeti; Raghunandan, Vulli (International Journal of Psychosocial Rehabilitation, 2024)
The Internet of Things (IoT) is a widely evolving platform tending to automate daily actions, thereby reducing the extent of human efforts. The aim is to find various methods using which Web intelligence & IoT can be enforced, taking into consideration efficiency and other economic constraints. This paper discusses the different methods that are adopted while applying Web intelligence techniques with IoT in various fields in the real world. Using various branches of Web Intelligence like Semantic Web, Information Retrieval and Data mining, the applications of IoT are explored